2022
DOI: 10.3389/feduc.2022.980445
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and communication in blended learning environments

Abstract: Blended learning environments have become increasingly common during the past few years, and frequent access to digital technologies has influenced many areas of learning and classroom interaction. This paper investigates teacher-pupil and pupil-pupil communication and collaboration practices in a leading-edge Norwegian primary school. In this small-scale case study, seven teachers were interviewed individually and in their respective grade level teams, and two grade levels were observed for a 4-week period to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Ref. [ 11 ] confirmed the usefulness of digital technology for communication and collaboration in learning environments through qualitative research with teachers. Ref.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Ref. [ 11 ] confirmed the usefulness of digital technology for communication and collaboration in learning environments through qualitative research with teachers. Ref.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Recently, digital textbooks have incorporated AR or VR technologies [ 7 ]. Communication functions refer to the features that facilitate interaction between teachers and learners or among learners [ 11 ], allowing for active collaboration in an online environment through posting and commenting on discussions or real-time communication. Features that allow students to upload and receive feedback on assignments enable them to comfortably complete and submit their work [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that group work strategies include active learning (Anosova et al, 2022;Ben-Eliyahu, 2021;Chuang, 2021), flipped classroom model (Julia et al, 2020;Mitsiou, 2019), problem-based learning (Dorit & Nirit, 2022;Shalini, 2021), simulation-based learning (Abrandt Dahlgren & Hopwood, 2023;Cho et al, 2022;Mammadova, 2021), interactive lecture (Taat et al, 2020;Zhampeiis et al, 2022), intensive learning (Boonteerarak, 2021), and ICT-based learning (Akorede & Adeniyi, 2020;Poplavskyi & Bondar, 2021). In the context of formation of communicative competency in the system of continuing education, self-study strategies refer to personalization (Bekmanova et al, 2021;Yoel et al, 2022;Shemshack & Spector, 2020), peer learning (Johler, 2022;Johnson et al, 2021), selfregulated learning (Lemmetty & Collin, 2020;Santoso et al, 2022), and placement (Caspersen & Smeby, 2021;Woods, 2021). Table 1 demonstrates the review on modern strategies and methods to form communicative competency in the system of continuing education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…tailoring the educational materials to learners' needs (Yoel et al, 2022); transformation of the teaching experience and students' learning experience to achieve educational goals (Shemshack & Spector, 2020) Instructional video (Schmid et al, 2022) Interactive testing (Bekmanova et al, 2021) Work with multimedia textbook (Bekmanova et al, 2021) Didactic cards (Villatoro & de-Benito, 2022) Work with documents (Bekmanova et al, 2021) Quiz and games (Shemshack & Spector, 2020;Villatoro & de-Benito, 2022) Storytelling (Shemshack & Spector, 2020) Concept test (Shemshack & Spector, 2020;Villatoro & de-Benito, 2022) Peer learning students' learning with and from each other (Johler, 2022); horizontal educational process when students participate in instruction and evaluation (Johnson et al, 2021) Warm-up activity (Duran et al, 2019) Collaborative work (Mantra et al, 2019) Reporting (Johler, 2022) Conference (Johler, 2022;Johnson et al, 2021) Preparation of information messages (Johnson et al, 2021) Picture description (San Martin et al, 2020) Parallel control (Mantra et al, 2019) Webinar (Yang & Kim, 2022) Independent practice (Mitsiou, 2019) Peer evaluation (Johler, 2022;Johnson et al, 2021) Self-regulated learning Involvement of students' into organization and control of the learning environment (Lemmetty & Collin, 2020); process when students actively manage their own learning experiences (Mejeh & Held, 2022); process when learners monitor and control their cognition, motivation, and ...…”
Section: Group Workmentioning
confidence: 99%